Validation of the Parent Health Locus of Control Scales in an Italian sample - Bornstein Marc H; Axia Giovanna; Bonichini Sabrina (BMC, 2009)
Abstract Aim This study examined the psychometric properties and the replicability of De Vellis's (1993) Parent Health Locus of Control (PHLOC) scales in an Italian sample. Method The Italian version of PHLOC was administered to 470 mothers of birth to 3-year-old children. Results Varimax rotated confirmatory factor analysis identified the six original subscales, namely Child, Divine, Fate, Media, Parental, and Professional influences over child health. Internal consistency of the subscales was good (α > .70), and test-retest correlations were adequate (r > .80). More highly educated mothers rated media influence as most important. No differences were found considering children's age, gender, and birth order. Conclusion The results offer good evidence of the cross-cultural validity of the PHLOC scales, an instrument that can be useful in interventions with families by the health care practitioners to prevent neglectful childrearing practices.